Pelatihan Bahasa Inggris Dan Seni Tari Bagi Remaja Masjid Tahfidz Al Qur'an Nurul Huda Di Nagari Panyalaian - Vonny Ardiel; Ira Maulina Sa’danoer; Dina Ayuning Tyas (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
English language skills are a skill that is needed in this era of globalization. English is the main communication tool in education and general interaction in national and international society. English training for youth Tahfidz Markazul Quran mosque Nurul Huda Nagari Panyalaian is one form of knowledge reference in the Babaliak ka Surau program. This English training uses the Gamification method, where the learning process uses the guessing game method, numbers, pictures and words. The purpose of using this method is to create a sense of pleasure and not get bored in learning, then it can attract the interest and motivation of participants in learning. Likewise with Pasambahan traditional dance training as a program to preserve and maintain Minangkabau cultural arts. The results of this activity are (1) an increase in interest and motivation in learning English. (2) Can add vocabulary in daily life (3) Can use basic English in communication (3) improve arts and culture skills, especially traditional dance. The evaluation of this activity shows that this activity has the support of the training participants and the mosque management and will become a follow-up program for the team. Therefore, this program is a form of activation of the Ba Baliak ka Surau program for youth in Nagari Panyalaian.